Egophoricity and Perspective: A View From Spoken Swedish - Bergqvist, Henrik (Frontiers in Communication, 2021)
From the point of view of everyday talk and especially, casual conversation, it is obvious that language use is highly perspectivized with a clear focus on the speech-act participants. This fact is supported by observations regarding the pervasiveness of egophoric pronouns and the frequent use of the modal particles ju and väl in spoken Swedish. The paper demonstrates how egophoric pronouns, modal particles, and mental verbs are used to signal the epistemic perspective of the speech-act participants, i.e., when the knowledge and attention of the speech-act participants are at stake. These formally distinct resources show patterns of co-distribution that permit an analysis of forms in terms of how they signal shared/private access to events from the perspective of the speaker and the addressee.